Pengatur Temperatur Minuman pada Dispenser Berbasis Mikrokontroler dengan Logika Fuzzy Mamdani - Saragih, Rafif Aprizki; R., Rakhmat Kurniawan (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The need for hot water is something that is needed in everyday life, with hot water it will facilitate the serving of drinks that are favored by the community such as coffee, milk and tea. However, in certain conditions, a person needs water with varying temperatures around 15°C to 95°C. Variations in water temperature needed in making drinks can affect the quality of the drinks served. The need for a temperature device on the dispenser to make it easier to adjust the water temperature. Dispensers with features that can control water temperature so that someone is easier to set how much water temperature is needed by combining hot and normal water into one output without having to mix, increase or decrease the volume. One of the control techniques that is often used today is control with Mamdani fuzzy logic. In this research, fuzzy controllers are used to keep the temperature stable. The water temperatures used in this dispenser are 65°C for tea, 75°C for milk and 90°C for coffee. The time required to reach the highest temperature of 90 from the normal temperature of 29.50 is 5 minutes. There is a temperature difference on the LCD display with a thermometer during testing, namely for tea 2.30%, milk 2.66% and coffee by 1.66%. These errors can occur due to the tolerance of the components used. From the test results, the application of fuzzy logic in the dispenser for temperature regulation is very effective in stabilizing the water temperature in tea, milk and coffee.